PARTISIPASI POLITIK PEREMPUAN DALAM AL-QUR’AN - Muhammad al-Caff; Siti Zinatun (Sekolah Tinggi Agama Islam (STAI) Sadra, 2016)
The issue of women’s political participation rarely finds a place in the Sunni and Shiite’s conventional jurisprudence thought, to imply that women should not have a political office and that their duties are solely rooted in the domestic sphere alone. In this case, one of the problems that deserves to employed in scholarly studies is the political rights of women according to the Qur’anic paradigm. Through the method of al-tafsīr al-jāmi’, this paper attempts to provide the scholarly debates concerning women’s political participation based on certain Qur’anic verses. This research shows three different major views concerning women’s political participation; the absolute prohibition, the absolute permission, and the alternative view. All are based on the interpretation of certain Qur’anic verses. The second is considered as more compatible with the principles of democracy. However, the significance of the different views concerning women’s political participation in the Qur’an lies on the fact that it has the holistic and multi-layered views on women’s political participation within each particular contexts accross the time, not a monolitic view limited to one alternataive